Evaluation of robustly optimised intensity modulated proton therapy for nasopharyngeal carcinoma. (March 2022) - Scandurra, Daniel; Meijer, Tineke W.H.; Free, Jeffrey; van den Hoek, Johanna G.M.; Kelder, Lotta; Oldehinkel, Edwin; Steenbakkers, Roel J.H.M.; Both, Stefan; Langendijk, Johannes A.
Highlights: First study to report clinical experiences using robustly optimised IMPT in nasopharyngeal cancer. Dose accumulation performed on robustly evaluated weekly repeat CTs for 25 patients. Plan adaptation rate was low (2/25 patients). Target coverage, critical organ maximum doses and NTCP were stable despite uncertainties and anatomy changes. Abstract: Background and purpose: To evaluate the dosimetric changes occurring over the treatment course for nasopharyngeal carcinoma (NPC) patients treated with robustly optimised intensity modulated proton therapy (IMPT). Materials and methods: 25 NPC patients were treated to two dose levels (CTV1: 70 Gy, CTV2: 54.25 Gy) with robustly optimised IMPT plans. Robustness evaluation was performed over 28 error scenarios using voxel-wise minimum distributions to assess target coverage and voxel-wise maximum distributions to assess possible hotspots and critical organ doses. Daily CBCT was used for positioning and weekly repeat CTs (rCT) were taken, on which the plan dose was recalculated and robustly evaluated. Deformable image registration was used to warp and accumulate the nominal, voxel-wise minimum and maximum rCT dose distributions. Changes to target coverage, critical organ and normal tissue dose between the accumulated and planned doses were investigated. Results: 2 patients required a plan adaptation due to reduced target coverage. The D98% in the accumulated voxel-wise minimum distribution was higher than planned for CTV1 in 24/25 patients and for CTV2 in 20/25 patients. Maximum doses to the critical organs remained acceptable in all patients. Other normal tissue doses showed some variation as a result of soft tissue deformations and weight change. Normal tissue complication probabilities for grade ≥ 2 dysphagia and grade ≥ 2 xerostomia remained similar to planned values. Conclusion: Robustly optimised IMPT plans, in combination with volumetric verification imaging and adaptive planning, provided robust target coverage and acceptable OAR dose variation in our NPC cohort when accumulated over longitudinal data.